Genesis and prospects of the Ukrainian stock market - Melekh, Yaroslav (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The article examines the formation and development of the Ukrainian stock market from 1991 to present. The author defines specific characteristics of the stock market in Ukraine, such as: the advantage of the primary market, issue of shares, a small proportion of the stock market, lack of awareness of investors about the debt securities, low guarantees on income payments on securities. The dynamics of financial instruments trading and index PFTS in recent years are analysed. The author also suggests ways of strengthening the competitiveness of the Ukrainian stock market: development of a comprehensive national strategy of economy capitalization of priority industries and enterprises; amending the current legislation to ensure effective state regulation of companies and industries and the formation of transparent property rights; development of a realistic long-term strategic plan for the economy and its individual sectors and enterprises for 15–20 years. At the same time, establishment of innovative model of development to set priority areas with regard to WTO accession and requirements to adapt to EU standards; ensuring transparency of companies’ financial reporting, timely publication and disclosing all required information on their activities; improvement of the implementation of agreements and tracking the ownership of securities.
Keywords: Ukraine; stock market; prospects